2022
DOI: 10.1111/1365-2664.14117
|View full text |Cite
|
Sign up to set email alerts
|

Integrating species metrics into biodiversity offsetting calculations to improve long‐term persistence

Abstract: 1. Several methods of measuring biodiversity in development-offset trades exist.However, there is little consensus on which biodiversity metrics should be used for quantifying development impacts and assigning offsets.2. We simulated development impacts in a virtual landscape and offset these impacts using six biodiversity metrics: vegetation area, vegetation condition, habitat suitability, species abundance, metapopulation connectivity and rarityweighted richness. We tested long-term impacts of metric choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This was particularly true for species typical of forested wetlands. Similar to other studies (Marshall et al, 2022; Maseyk et al, 2016), our results indicate that simple, aggregated offset currencies like area fail to account for individual biodiversity elements during trades. This is a consequence of nonequivalence of species composition between impacted wetlands and banks.…”
Section: Discussionsupporting
confidence: 89%
“…This was particularly true for species typical of forested wetlands. Similar to other studies (Marshall et al, 2022; Maseyk et al, 2016), our results indicate that simple, aggregated offset currencies like area fail to account for individual biodiversity elements during trades. This is a consequence of nonequivalence of species composition between impacted wetlands and banks.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, many policies demonstrate a dichotomy where designing offsets requires that developers consider which species or communities are likely to be affected but not to measure anything, which might help inform conservation actions designed to protect them (Gibbons & Lindenmayer, 2007;Maron et al, 2010). Recent research has demonstrated the risks of ignoring such metrics on species persistence, emphasizing further that inadequate measurement of biodiversity may speed up declines in the populations or ecosystems offsets were originally designed to conserve (Buschke, 2017;Marshall et al, 2021Marshall et al, , 2022. This risk is further compounded by a lack of transparency we observed here in terms of how these metrics are scored and combined to get an overall picture of biodiversity impacts (Kujala et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of scientific literature demonstrating that the habitat‐based biodiversity metrics used during offsetting generally fail to capture development impacts, particularly on species and communities (Cristescu et al., 2013; Hanford et al., 2016; Marshall et al., 2022). Over time, reliance on metrics, which do not accurately measure development impacts on species and populations, will ensure offsets fail to deliver their claimed benefits and perpetuate biodiversity declines (Josefsson et al., 2021; Marshall et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since biodiversity is interconnected and directly or indirectly affects various ecosystem functions [62], it has the potential to be used solely or as one of the proxies. If biodiversity is to be used as a proxy for ecosystem function, it is crucial to use appropriate metrics which capture all the important biodiversity attributes [63]. However, we recommend developing a sound methodology to rank the important ecosystem functions (preferably readily measurable) and identify the few ecosystem functions which can be used as proxies to indicate the achievement of ecological compensation goals.…”
Section: Ecological Compensation Of Ecosystem Functionsmentioning
confidence: 99%